Filler for oil-based ink and pigment composition for oil-based ink
Precipitated amorphous silica with specific properties is used in oil-based ink to enhance hiding power and wettability, addressing the challenge of high pigment sedimentation and cost in existing technologies.
Patent Information
- Application Number
- JP2020177530
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-10-25
- Filing Date
- 2020-10-22
- Publication Date
- 2025-01-06
- Estimated Expiration
- 2040-10-22
AI Technical Summary
Existing ink fillers struggle to achieve high hiding power while minimizing the use of expensive white pigments like titanium oxide, which have high sedimentation properties, and conventional methods fail to uniformly disperse these pigments without increasing their amount.
The use of precipitated amorphous silica with a specific particle size range (0.8-4.0 μm) and BET specific surface area (5-300 m²/g) as a filler in oil-based ink, combined with white pigments, enhances hiding power by improving light scattering and wettability, allowing for reduced pigment usage.
The precipitated amorphous silica filler achieves high hiding power and improved wettability with white pigments, reducing the amount of expensive pigments needed while maintaining stability and dispersibility.
Smart Images

Figure 0007608110000005 
Figure 0007608110000006 
Figure 0007608110000007
Abstract
Description
[Technical field]
[0001] The present invention relates to a filler for oil-based inks comprising precipitated amorphous silica, and further to a pigment composition for oil-based inks containing the filler. [Background technology]
[0002] Silica particles have been incorporated into ink fillers in the past, but only for the purpose of imparting a matte or matte finish (see Patent Document 1).
[0003] On the other hand, when the ink is printed on a transparent or colored recording medium, it is necessary to reduce the transparency of the transparent recording medium or to conceal the color of the colored recording medium during printing. When such concealment is required, a pigment such as titanium oxide is used.
[0004] When it is desired to improve the hiding power of the ink, it is possible to increase the amount of pigment blended, but since pigments such as titanium oxide have a high tendency to settle, it is practically desirable to avoid blending a large amount. For example, Patent Document 2 discloses a hiding ink composition in which hiding composite particles containing titanium oxide and / or zinc oxide particles are blended in a solution in which ultrafine inorganic particles (e.g., fumed silica) having a particle size of 0.008 to 0.05 μm are dispersed.
[0005] However, in the concealing ink composition of Patent Document 2, the ultrafine inorganic microparticles are used to prevent the settling of the concealing composite particles, which have a large particle size. Although the use of such inorganic microparticles enables the concealing composite particles to be uniformly dispersed in the ink and a stable concealing power to be exerted, it is not possible to reduce the amount of the concealing composite particles used and achieve high concealing power. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Japanese Unexamined Patent Publication No. 1-174574 [Patent Document 2] JP 2006-316193 A Summary of the Invention [Problem to be solved by the invention]
[0007] SUMMARY OF THE PRESENT EMBODIMENT An object of the present invention is to provide a filler for oil-based inks which exhibits high hiding power. Another object of the present invention is to provide a filler for oil-based inks which, when used in combination with a white pigment, can ensure high hiding power while reducing the amount of expensive white pigment used. A further object of the present invention is to provide a pigment composition for oil-based inks, which contains the above-mentioned filler for oil-based inks and a white pigment. [Means for solving the problem]
[0008] According to the present invention, the volume-based average particle size (D 50 ) is 0.8 to 4.0 μm, and the BET specific surface area is 5 to 300 m 2 The present invention provides a filler for oil-based inks comprising precipitated amorphous silica having a molecular weight in the range of 0.1 to 1.0 μm / g.
[0009] In the oil-based ink filler of the present invention, (1) The BET specific surface area is 5 to 200 m 2 / g, (2) The chlorine content is in the range of 200 to 3,000 ppm. (3) The precipitated amorphous silica has an ignition loss (1050°C, 1 hr) of 4% or more. is preferred.
[0010] According to the present invention, there is also provided a pigment composition for oil-based inks, which contains the above-mentioned filler for oil-based inks and a white pigment.
[0011] In the oil-based ink composition, (1) The precipitated amorphous silica is blended in an amount of 5 to 200 parts by mass per 100 parts by mass of the white pigment; (2) The white pigment is titanium oxide or zinc oxide; (3) It is incorporated into oil-based inks used in screen printing. is preferred. Effect of the Invention
[0012] The oil-based ink filler of the present invention (precipitated amorphous silica) exhibits high hiding power, and when used in combination with a white pigment in particular, it is possible to ensure high hiding power while reducing the amount of expensive white pigment used. Such high hiding power has been discovered as a phenomenon through many experiments, and although the reason has not yet been precisely elucidated, the present inventors presume it to be as follows.
[0013] That is, in the present invention, the amorphous silica used as a filler for oil-based inks is obtained by a precipitation method, and therefore has a larger volume-based average particle size in the range of 0.8 to 4.0 μm compared to ultrafine silica (fumed silica) obtained by a dry method. It is presumed that an aggregate of particles of this size allows light to easily enter the interior of the particle, and thus the light is easily scattered inside the particle, resulting in a high hiding power.
[0014] In addition, this precipitated amorphous silica has a relatively large BET specific surface area in relation to the average particle size described above, and is in the range of 5 to 300 m 2 / g, especially 5 to 200m 2 / g. That is, it is believed that the high wettability is associated with the distribution of many SiOH groups on the surface, and as a result, the affinity with white pigments such as titanium oxide and zinc oxide is improved, and these white pigments are distributed on the amorphous silica surface, the white pigments are increased in volume, and high hiding power is ensured while reducing the amount of white pigment blended.
[0015] Therefore, the oil-based ink filler of the present invention can exhibit its properties to the maximum extent by being mixed with a white pigment and incorporated into an oil-based ink. [Brief description of the drawings]
[0016] [Figure 1] This figure shows the results of a coating wettability test (after 5 seconds) using a dyne pen (35 mN / m and 32 mN / m pens) for a paint containing 30 parts of titanium dioxide. [Diagram 2] This figure shows the results of a coating wettability test (after 60 seconds) using a dyne pen (35 mN / m and 32 mN / m pens) for a paint containing 30 parts of titanium dioxide. [Diagram 3] FIG. 1 shows the results of a coating wettability test (after 5 seconds) using a dyne pen (35 mN / m and 32 mN / m pens) for a paint containing 10 parts by mass of amorphous silica A and 20 parts by mass of titanium oxide in Example 1. [Figure 4] FIG. 1 shows the results of a coating wettability test (after 60 seconds) using a dyne pen (35 mN / m and 32 mN / m pens) for a paint containing 10 parts by mass of amorphous silica A and 20 parts by mass of titanium oxide in Example 1. [Diagram 5] FIG. 1 shows the results of a coating wettability test (after 5 seconds) using a dyne pen (35 mN / m and 32 mN / m pens) for a paint containing 2.5 parts by mass of amorphous silica B and 27.5 parts by mass of titanium oxide in Comparative Example 1. [Figure 6] FIG. 1 shows the results of a coating wettability test (after 60 seconds) using a dyne pen (35 mN / m and 32 mN / m pens) for a paint containing 2.5 parts by mass of amorphous silica B and 27.5 parts by mass of titanium oxide in Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] [Precipitated amorphous silica] The precipitated amorphous silica used as the oil-based ink filler in the present invention has a BET specific surface area of 5 to 300 m 2 / g, preferably 5 to 200m 2 / g, particularly preferably 50 to 100m 2 The primary particle diameter calculated from the BET specific surface area is in the range of 8 to 300 nm, preferably 8 to 30 nm, and particularly preferably 15 to 30 nm. The precipitated amorphous silica has an average particle size (D 50 ) is in the range of 0.8 to 4.0 μm, preferably 0.8 to 3.1 μm.
[0018] For example, if the average particle size is smaller than the above range or the BET specific surface area is larger than the above range, the light is less likely to enter the particles, and the light is less likely to scatter inside the particles, resulting in a decrease in hiding power. On the other hand, if the average particle size is larger than the above range, the dispersibility in white pigments and oil-based inks is impaired, making it difficult to achieve stable hiding power. In addition, even if the BET specific surface area is smaller than the above range, there is no particular advantage and it is merely economically disadvantageous.
[0019] In addition, in the present invention, the above-mentioned precipitation method amorphous silica is often produced using chlorides such as salt, and in this case, the chlorine content is in the range of 200 to 3000 ppm. That is, even if the amorphous silica is obtained by precipitation method, the chlorine content of the one obtained without using chlorides is derived from the inevitable impurities contained in the raw material (e.g., alkali silicate, etc.) used, so the chlorine content is lower than the above range.
[0020] The precipitation method is a so-called wet method using alkali silicate as the main raw material, and the obtained amorphous silica has a large ignition loss of 4% or more, particularly 5% or more (1050°C, 1 hr), unlike the ultrafine silica obtained by the dry method described in Patent Document 2, etc. Such a large ignition loss is thought to be one of the factors that results in high wettability. Furthermore, in the conventional precipitation method, once the silica sol particles are formed, silicic acid ions are bonded to the surface silanol groups and the amorphous silica grows slowly, so that the ignition loss of this amorphous silica is 3% or less. In contrast, in the amorphous silica filler of the present invention, an alkali silicate and a mineral acid are simultaneously poured into a concentrated electrolyte salt solution. The low molecular weight silicic acid ion species formed undergoes rapid dehydration condensation and polymerization due to the strong salting out action of the mineral acid ions and the electrolyte salt, and grows into a polymeric silicic acid, which is a fine silica gel, without passing through silica sol particles. This increases the number of silanol groups, and the amorphous silica of the present invention obtained has a large ignition loss of 4% or more, especially 5% or more (1050°C, 1hr). It is believed that such a large ignition loss is one of the factors that bring about high wettability.
[0021] This precipitated amorphous silica has a relatively low bulk density due to its manufacturing method. For example, the bulk density measured by the iron cylinder method (JIS K 6220-1 7.8.2:2015) is 0.16 to 0.36 g / cm 3 , preferably 0.16 to 0.22 g / cm 3 , particularly preferably 0.18 to 0.22 g / cm 3 Such a bulk density causes light scattering, which is considered to be one of the factors that results in a large hiding power.
[0022] The precipitated amorphous silica has an oil absorption (JIS K 5101-13-1:2004) of 180 ml / 100 g or less, preferably 150 ml / 100 g or less, and particularly preferably 100 ml / 100 g or less. If the oil absorption is high, when the precipitated amorphous silica is added to an ink solution, the solution thickens and the coatability deteriorates.
[0023] [Precipitated amorphous silica manufacturing method] The amorphous silica of the present invention used as a filler for oil-based inks is obtained by the precipitation method, as already described. In general, this method involves neutralizing an alkali silicate and an acid to precipitate silica particles. For example, this can be done by pouring an alkali silicate and a mineral acid into water or an aqueous electrolyte solution with stirring to carry out the neutralization reaction.
[0024] Examples of the alkali silicate include those represented by the following formula (1); M 2 O nSiO 2 (1) In the formula, M is an alkali metal such as Na or K. n is a number between 1 and 3.8. From an economical point of view, it is preferable to use so-called No. 3 sodium silicate, in which the number n is in the range of 3.0 to 3.4. There is no particular limitation on the concentration of the aqueous alkali silicate solution used in the reaction, but it is generally preferable to use the aqueous solution at a concentration of 5 to 35% by mass.
[0025] As the mineral acid, an aqueous solution of hydrochloric acid, nitric acid, sulfuric acid, phosphoric acid, etc. is used, and although an aqueous solution of hydrochloric acid or sulfuric acid is generally used, in the present invention, hydrochloric acid is optimal from the viewpoint of increasing the concentration of SiOH groups on the surface. The acid concentration of the aqueous acid solution is usually about 5 to 20 mass%.
[0026] The electrolyte aqueous solution to which the alkali silicate and mineral acid are added is not particularly limited, but may be an aqueous solution of an electrolyte salt such as sodium phosphate, ammonium sulfate, sodium chloride, sodium sulfate, lithium chloride, lithium sulfate, sodium carbonate, sodium hydrogen carbonate, etc., and preferably sodium chloride is used. The use of such an electrolyte promotes the aggregation and growth of silica particles, making it possible to obtain amorphous silica with the desired physical properties. The concentration of such an aqueous electrolyte salt solution may usually be 1% by mass or more, particularly about 5 to 15% by mass, at the start of the neutralization reaction.
[0027] The order of pouring the alkali silicate and the mineral acid during the neutralization reaction is preferably a method of pouring the alkali silicate aqueous solution and the acid aqueous solution simultaneously, but the acid aqueous solution can also be poured after the alkali silicate aqueous solution. It is preferable to control the pH at this reaction stage. For example, it is good to maintain the pH in the range of 6 to 10, preferably 8 to 9.5 during the simultaneous pouring. If the pH is higher than this range, the metathesis reaction does not proceed, and it becomes difficult to produce silica particles as nuclei. On the other hand, if the pH is lower than the above range, the reaction proceeds all at once, silica particles are precipitated all at once, and it may not be possible to obtain amorphous silica with the desired characteristics. In addition, the reaction temperature in this step is usually preferably in the range of 40 to 90°C.
[0028] After the reaction is completed, the mixture is aged to precipitate amorphous silica particles. The pH during this aging is generally in the range of 4 to 10, particularly 5 to 8. If the pH is outside the above range, the precipitation does not proceed effectively, and it may be difficult to obtain silica particles with the desired characteristics. The pH adjustment at this stage can be easily performed, for example, by simply pouring a predetermined amount of mineral acid after stopping the addition of the alkali silicate. The aging time varies depending on the amount of the alkali silicate used, but is generally about 30 to 60 minutes at a temperature of 50 to 100°C.
[0029] After aging, the silica slurry containing the produced silica (usually SiO 2 The target amorphous silica can be obtained by subjecting the resulting solution having a concentration of 1 to 10% by mass to processes of dealkalization, filtration, water washing, drying and pulverization. The dealkalization, filtration, and washing are carried out according to a standard method to remove by-products such as alkali salts or electrolyte salts. For example, the dealkalization can be carried out by adding a mineral acid to adjust the pH to a range of about 2 to 4.
[0030] When sodium chloride is used as the metal salt and hydrochloric acid is used as the acid for neutralization, the resulting amorphous silica has a high chlorine content, which may reach, for example, a maximum of 3000 ppm. In order to reduce this chlorine content, thorough washing with water is sufficient. By thorough washing with water, the chlorine content can be reduced to about 200 ppm. In addition, such thorough washing with water tends to slightly increase the specific surface area, and for example, the specific surface area of 200 m 2 / g, the BET specific surface area is 300m 2 / g.
[0031] Drying is performed by heat treatment at about 100 to 300° C., and the amorphous silica after washing and drying is crushed to a predetermined particle size and classified to produce a product. For such crushing, a jet crusher, an impact crusher, a vibration crusher, etc. are used, and for classification, a gravity type wind classifier, an inertia type wind classifier, a centrifugal type wind classifier, a mechanical type wind classifier, etc. are used.
[0032] [Oil-based ink] When the ink is required to have a hiding property, a white pigment is usually used as the pigment, and therefore the filler of the present invention is preferably used in combination with a white pigment. For example, it is preferable to prepare a pigment composition by mixing the white pigment with the white pigment in an amount of 5 to 200 parts by mass, particularly 20 to 100 parts by mass, per 100 parts by mass of the white pigment, and then blending the pigment composition in an oil-based ink solution, thereby ensuring high hiding power while reducing the amount of expensive white pigment used.
[0033] Examples of the white pigment include metal oxides, barium sulfate, calcium carbonate, and other metal compounds. Examples of the metal oxide include titanium oxide, zinc oxide, alumina, magnesium oxide, and other. From the viewpoint of high hiding power, the white pigment to be used in combination with the filler of the present invention is preferably titanium oxide or zinc oxide, and most preferably titanium oxide.
[0034] The oil-based ink in which the filler of the present invention, for example, a pigment composition containing the filler of the present invention, is blended is not particularly limited, and can be applied to known oil-based inks such as photocurable, heat-curable, and ultraviolet-curable inks. The method for forming a coating film using the ink containing the filler of the present invention is not particularly limited, and any ordinary coating method can be applied. Specifically, various coating methods such as stencil printing such as screen printing, intaglio printing such as gravure printing, or roll coating can be applied.
[0035] The applications of the ink containing the filler of the present invention are not particularly limited. For example, the ink can be used to coat the picture frames of displays for mobile devices, taking advantage of its excellent hiding power. Typically, the substrate of such displays is made of glass, and in order to achieve sufficient light-blocking properties, multiple layers of coating are required. However, the ink containing the filler of the present invention has excellent light-blocking properties, making it possible to reduce the number of times that coating is required. EXAMPLES
[0036] The excellent effects of the present invention will be explained by the following experimental examples. In the following experiments, various measurements were carried out by the following methods.
[0037] (1) Volume-based average particle size (D 50 ) The measurement was performed by a laser diffraction scattering method using a Malvern Mastersizer 3000.
[0038] (2) BET specific surface area and primary particle size Measurement was performed by nitrogen adsorption method using a Tristar II 3020 manufactured by Shimadzu Corporation, and the specific surface area was measured by the BET method. Note that pretreatment was performed under reduced pressure conditions at 150°C for 2 hours. Further, the primary particle diameter d was calculated from the BET specific surface area by the following formula. d=6 / ρS ρ: density of silica S:BET specific surface area
[0039] (3) Bulk density (apparent specific gravity): Iron cylinder method Measurements were performed in accordance with JIS K 6220-1 7.8.2:2015.
[0040] (4)Ignition loss Ignition loss was determined by measuring the residual weight after drying a sample at 110°C for 2 hours, igniting it at 1050°C for 1 hour, and then allowing it to cool.
[0041] (5) Oil absorption amount Measurements were performed in accordance with JIS K 5101-13-1:2004.
[0042] (6) Measurement of chlorine content 3 g of the sample was dispersed in 90 g of water and boiled for 1 hour. The liquid was centrifuged and the supernatant was filtered. The chlorine content of the filtrate was then quantified using a Prominence high performance liquid chromatograph manufactured by Shimadzu Corporation.
[0043] (7) Concealment In accordance with JIS K 5101-4 (Testing methods for pigments - Part 4), the powder sample was dispersed in a clear urethane paint and applied to a hiding rate test paper. The hiding rate was calculated from the tristimulus value Y value of the white and black parts of the test paper using a Nippon Denshoku Industries Co., Ltd. spectrophotometer / color difference meter PF-7000.
[0044] (8) Wettability The evaluation was carried out in accordance with JIS K 6768:1999 (Plastic films and sheets - Wet tension test method) using a dyne pen with a dyne level (surface energy value) of 32 mN / m and 35 mN / m. Specifically, lines were drawn simultaneously on the coating using pens with dyne levels of 32 mN / m and 35 mN / m, and the condition of the drawn lines was observed 5 seconds and 60 seconds later and evaluated on the following three-level scale. ○: The drawn line is held stable without turning into water droplets. △: A few droplets are observed along the drawn line, but the line shape is maintained. ×: Water droplets are clearly observed along the drawn line, the line has become thinner, and parts of it are missing. The higher the dyne level, the greater the adhesion (wettability).
[0045] <Example 1> Precipitated amorphous silica A was produced by the following method. A sodium silicate solution (Na 2 O 7% by mass, SiO 2 22% by mass and 14% by mass hydrochloric acid were simultaneously poured into the reaction solution for 6 hours while maintaining the pH of the reaction solution at 4 to 6. Next, the pH of the reaction solution was adjusted to 3 to 5 with hydrochloric acid, aged, filtered, and washed with warm water at 50° C. The cake obtained by washing with hot water at 50° C. was dried at 120° C. to 140° C. and then pulverized to obtain precipitated amorphous silica A.
[0046] <Comparative Example 1> Precipitated amorphous silica B was produced by the following method. Sodium silicate solution (Na 2 O 7% by mass, SiO 2 22% by mass and 14% by mass sulfuric acid were simultaneously poured into the reaction solution for 9 hours while maintaining the pH of the reaction solution at 7 to 9. Next, the pH of the reaction solution was adjusted to 2 to 4 with sulfuric acid, aged, filtered, and washed with warm water at 50° C. The cake obtained by washing with hot water at 50° C. was dried at 120° C. to 140° C. and then pulverized to obtain precipitated amorphous silica B.
[0047] Various physical properties of the amorphous silica A and amorphous silica B produced above were measured, and the results are shown in Table 1.
[0048] [Table 1]
[0049] <Concealment rate evaluation test> For the amorphous silica A produced in Example 1 and the amorphous silica B produced in Comparative Example 1, a hiding rate evaluation test was carried out. Specifically, 20 parts by mass and 30 parts by mass of sample amorphous silica A or B per 100 parts by mass of paint were dispersed in a clear urethane paint, and the hiding ratio was measured. The results are shown in Tables 2 and 3. When 20 parts by mass was blended, a 450 μm applicator was used, and when 30 parts by mass was blended, a 250 μm applicator was used. In addition, when 30 parts by mass of amorphous silica B (amorphous silica produced in Comparative Example 1) was blended, the paint thickened significantly and could not be applied, so that the hiding rate could not be measured.
[0050] [Table 2]
[0051] [Table 3]
[0052] In addition, the 60° gloss and hiding ratio of the coating film were measured when 30 parts by mass of titanium oxide, a white pigment, was blended into a clear urethane paint. Furthermore, a portion of the titanium oxide was replaced with amorphous silica A (Example 1) and amorphous silica B (Comparative Example 1) so that the 60° gloss was equivalent, and the 60° gloss and hiding ratio at these times are shown in Table 4.
[0053] [Table 4]
[0054] As shown in Table 4, when the gloss value was equivalent, amorphous silica A of Example 1 showed a high hiding rate of 96% even when replacing one-third (10 parts by mass) of titanium oxide, whereas amorphous silica B of Comparative Example 1 showed a hiding rate lower than that of Example 1 when only 2.5 parts by mass out of 30 parts by mass were replaced.
[0055] <Wettability evaluation test> For each of the paints used in the gloss measurements shown in Table 4, the wettability of the coating film was evaluated after 5 seconds and 60 seconds using a dyne pen of 32 mN / m and 35 mN / m. The results are shown below. Photographs of each coating film taken after 5 seconds and 60 seconds are shown in Figs. 1 to 6.
[0056] Urethane paint containing 30 parts by weight of titanium dioxide; 35mN / m pen coating 5 seconds later: × After 60 seconds: × 32mN / m pen coating Evaluation after 5 seconds: Good Evaluation after 60 seconds: Good
[0057] A urethane paint containing a pigment composition obtained by mixing 20 parts by mass of titanium oxide and 10 parts by mass of amorphous silica A (Example 1); 35mN / m pen coating Evaluation after 5 seconds: Good Evaluation after 60 seconds: Good 32mN / m pen coating Evaluation after 5 seconds: Good Evaluation after 60 seconds: Good
[0058] A urethane paint containing a pigment composition obtained by mixing 27.5 parts by mass of titanium oxide and 2.5 parts by mass of amorphous silica B (Comparative Example 1); 35mN / m pen coating 5 seconds later: △ After 60 seconds: × 32mN / m pen coating Evaluation after 5 seconds: Good Evaluation after 60 seconds: Good
[0059] From the above results, the wettability of titanium oxide <比較例1<実施例1の順で高くなっており、経時によって、この差はより顕著になっていることが判る。即ち、本発明の非晶質シリカおよび白色顔料を含む油性インク用組成物は、隠蔽率が高いだけではなく、濡れ性も高い。 In addition, in Comparative Example 1, if the amount of amorphous silica B added is increased, it is expected that the wettability will be improved, but in this case, problems such as a decrease in the hiding ratio and an increase in viscosity will occur.< / 比較例1<実施例1の順で高くなっており、経時によって、この差はより顕著になっていることが判る。即ち、本発明の非晶質シリカおよび白色顔料を含む油性インク用組成物は、隠蔽率が高いだけではなく、濡れ性も高い。
Claims
1. The volume-based average particle size (D) measured by the laser diffraction scattering method 50 ) is 0.8 to 4.0 μm, and the BET specific surface area is 5 to 300 m 2 / g, has an ignition loss (1050°C, 1 hr) of 4% or more, and has a bulk density (JIS K 6220-1 7.8.2:2015) of 0.16 to 0.36 g / cm 3 1. An oil-based ink filler comprising precipitated amorphous silica,
2. The BET specific surface area is 5 to 200 m 2 2. The oil-based ink filler according to claim 1, wherein the molecular weight of the filler is 1 / g.
3. 3. The oil-based ink filler according to claim 1, wherein the chlorine content is in the range of 200 to 3,000 ppm.
4. 4. A pigment composition for oil-based inks, comprising the oil-based ink filler according to claim 1 and a white pigment.
5. 5. The pigment composition for oil-based inks according to claim 4, wherein the precipitated amorphous silica is blended in an amount of 5 to 200 parts by mass per 100 parts by mass of the white pigment.
6. 6. The pigment composition for oil-based ink according to claim 4, wherein the white pigment is titanium oxide or zinc oxide.
7. 7. The pigment composition for oil-based ink according to claim 4, which is incorporated into an oil-based ink used for screen printing.
Citation Information
Patent Citations
Ink composition for screen printing
JP1989174574A
Production of granular amorphous silica
JP1995081930A
Production of granular amorphous silica
JP1995232911A
Concealing ink composition
JP2006316193A
Overprint varnish composition for offset, and printed matter
JP2010229302A
